Identity and internet: (de)construction of communication and gender in social networks (Comunicação & Inovação, 2016)
This study is based on the experiences and communicational exchanges made on the Internet and how they influence the life and the construction of the identity of young people, especially considering the influences of the social field and the gender relations, both operationalized among the relations established on-line and off-line and involve the subjectivity of the subjects and their relationship with the Other.